Changing trends in blood transfusion: an analysis of 244, 013 hospitalizations. Issue 10 (14th April 2014) - Shehata, Nadine; Forster, Alan; Lawrence, Nadine; Rothwell, Deanna M.; Fergusson, Dean; Tinmouth, Alan; Wilson, Kumanan
Abstract : Background: Identifying recipients of blood transfusion and the trends in transfusion are needed to properly identify and target clinical services in need of patient blood management strategies. We determined the proportion of admissions to each clinical service that received blood, the mean number of units utilized, and the 5‐year trends in utilization. Study Design and Methods: We used a large administrative database, a repository for three campuses of one university‐affiliated hospital, and included all adults that were hospitalized from November 1, 2006, to June 2012. The data were analyzed as the proportion of admissions transfused and the mean number units transfused per admission. Results: Of 244, 013 hospitalizations, 38, 265 received at least one transfusion (29, 165 for red blood cells [RBCs], 6760 for plasma, and 5795 for platelets [PLTs]). Although there has been a gradual decrease in the mean number of RBCs transfused (percent change, −9.8%; p = 0.002), an increase in the proportion of admissions receiving RBCs (17.2% increase, p < 0.0001) and PLTs (31.5% increase, p < 0.0001) was apparent while there has been a decrease in the proportion of admissions receiving plasma (23.9% decrease, p < 0.0001). Eight percent of cardiology admissions received RBCs, and the highest mean RBC utilization per admission, aside from the stem cell transplantation service, occurred in cardiology and critical care hospitalizations (mean, 4.7 units/hospitalization). Conclusion: Although there has been a reduction in the mean RBC units used, there has been an increase in the proportion of hospitalizations transfused. A better understanding of the indications for transfusion is required to facilitate the development of targeted blood conservation strategies.